PERTOBATAN : JALAN MANUSIA MENEMUKAN KEINDAHAN YANG SEJATI - Agus Edy Cahyono (Jurnal Orientasi Baru, 2015)
A man is created as image of God (Imago Dei) so he has beauty as attribute of God. For his sin and weakness, beauty is polluted, he is fell into vulnerable and superficial. He is far from his dignity especially from image of God. The way to make his beauty come back is a repentance. A man keeps repenting in process in order to be united with God, the source of beauty. Repentance is not easy because a man sometime is trapped into artificial beauty and satisfied in appearance. The way to come back on an eternal beauty is difficult. A man just does not give a beauty of God but he needs to find a way to be united with God so he goes forward to An eternal beauty.